The Reformulation of Genre and Register Analysis - Jacek Kołata (Styles of Communication, 2010)
The aim of this article is to present and describe a new approach to Genre and Register Analysis in order to make the method more efficient and reliable. While gathering all necessary quotations, it occurred to me that it is extremely easy to look for a part of a particular article which would absolutely comprise Eggins and Martin’s areas of differences between texts. The question which should be raised at that point is whether the method should play the role of a guide, providing us with a commonly and acceptable way of interpreting all texts, or perhaps we should analyze only those samples of texts which would totally agree with all its guidelines. It is obvious that the second way of dealing with a problem is against all real scientific analyses. Therefore, I have decided to reformulate the above-mentioned analysis. Whether my method is better than some of its predecessors, is for the critics to judge, but the truth is that I would not transform Genre and Register Analysis if I had not believed that it could be.